At Hesitant Doors: The lived experience of women in STEM - Romina B. da Costa (University of Bologna, 2016)
This phenomenological investigation aims to explore the lived experience of women in Science, Technology, Engineering and Mathematics (STEM) disciplines. As a minority group within a traditionally male-dominated space, women are still underrepresented in the upper echelons of science, even if the number of women in STEM is increasing. The author draws from her experiences as an "undesirable statistic," a woman who entered college as a STEM student but ended up getting a degree in the social sciences. The author attempts to gain some new insights and understanding of the issue of women in STEM, engaging in two in-depth phenomenological conversations with a female engineering student in a large public university of US Mid-Atlantic region.